Revitalization of Nyai Sedapu Boja Kendal Tomb as a Cultural-Based Religious Tourism Epicenter - Afiah, Kumala Nur; Hakim, Lukmanul; Susanto, Dedy; Prihatiningtyas, Siti (Institut Agama Islam Negeri (IAIN) Curup, 2025)
Revitalization of culture-based religious sites is an important approach in developing sustainable and local value-based tourist destinations. This research aims to analyze the revitalization strategy of the Tomb of Nyai Sedapu as the epicenter of culture-based religious tourism in Boja, Kendal by referring to the principles of good governance in governance. This research uses a qualitative approach with the methods of observation, semi-structured interviews, and documentation. The results showed that revitalization was carried out through physical development and preservation of cultural values through local traditions. Community participation, legality of management through the village government, and information disclosure are real practices of transparency, accountability and rule of law. However, challenges remain in the limitations of digital promotion and budget support. This research shows that the management of religious sites that apply the principles of good governance can be an alternative model in the development of cultural and spiritual-based tourism.